Water for elephants [videorecording (DVD)] - Lawrence, Francis; Witherspoon, Reese, 1976-; Pattinson, Robert, 1986-; Waltz, Christoph, 1956-; Schneider, Paul, 1976-; Holbrook, Hal; Gruen, Sara (20th Century Fox Home Entertainment, 2011)
Against all odds, a veterinary student and a beautiful circus performer from a bygone era meet and fall in love through their shared compassion for a special elephant. But their secret romance incurs the wrath of her dangerously volatile husband.